Perceptions of Customer Incivility, Job Satisfaction, Supervisor Support, and Participative Climate: A Multi-Level Approach - Pap, Zselyke; Vîrgă, Delia; Notelaers, Guy (Frontiers in Psychology, 2021)
Perceived customer incivility can be a significant day-to-day demand that affects frontline service employees’ job satisfaction. The current research focuses on job resources on multiple levels that serve as buffers in the face of this demand. We tested a multi-level model in which supervisor support (at the employee level) and participative climate (at the work-unit level) moderate the negative relationship between perceived customer incivility and job satisfaction. We used multi-level analysis with self-reported cross-sectional data collected from 934 employees nested in 107 work units of a large clothing shop chain in Belgium. The results showed that both supervisor support and participative climate moderate the negative relationship between perceived customer incivility and job satisfaction. The theoretical contribution of this study resides in an extension of the JD-R theory to simultaneously conceptualize resources on multiple levels. In the meantime, we focus on practical, hands-on resources that organizations can implement to protect service employees from the adverse effects of perceived customer incivility.